Searching for Jossie: reserve and (sub)surface in the layered landscape of Langsett and Midhope. Issue 3 (3rd July 2019) - Walker Barker, David; Eltringham, Daniel
ABSTRACT: This creative-critical collaboration between the artist David Walker Barker and poet Daniel Eltringham explores the Pennine reservoir landscapes and drowned communities of Langsett and Midhope, 10 miles north-west of Sheffield. Their cabinet artwork Searching for Jossie comprises objects found on walks in those landscapes with text-and-image slates that work archival photographs and Eltringham's sequence R/S Res . into a textured surface. This hybrid essay delves into these landscapes' geology, ecology and human histories, in a dialogic mixed form placed in conversation with selected slates from Searching for Jossie . Walker Barker and Eltringham's cabinet is a playful take on the elusive 'Jossie cabin' that gives the work its title: a vanished shepherd's hut that stood on the moorland above Langsett Reservoir. As imaginative reconstructions of a scarcely legible landscape marked by loss, artwork, poem and essay interrogate a poetics of reserve and resource, surface and substratum, in this complex, layered landscape.